Emission rates of biogenic VOCs by thermal desorption tube and GC-MS near Cataract Scout Park, Australia taken during the COALA-2020 campaign - Malcolm Possell; Danica Parnell; Alex Guenther; Jhonathan Ramirez-Gamboa; Hamish McDougall; Clare Paton-Walsh; Jack B Simmons (PANGAEA, 2021)
Measurements of emission rates (μg/g/h) of volatile organic compounds were captured using thermal desorption tubes from a Teflon enclosure. Measurements were taken at Cataract Scout Park, Appin, N.S.W. (34°14 extquotesingle42.29"S 150°49 extquotesingle24.97"E) as part of the Characterizing Organics and Aerosol Loading over Australia (COALA-2020) campaign. Enclosures captured branches of select local tree species. Branch level VOC samples were made using a custom built, 9L branch enclosure. The two ends of the chamber were made from polytetrafluoroethylene (PTFE) supporting a transparent enclosure made from polyvinyl fluoride film (Dupont Chemicals, Macquarie Park, NSW, Australia). Ambient air, passed through an activated charcoal scrubber, was supplied to the chamber at 12 L/min using a mass flow controller (Aalborg, Orangeburg, NY, USA). Temperatures inside and outside the chamber were recorded manually every 5 minutes using a Digitech thermocouple thermometer with type K thermocouples (Jaycar Electronics, Rydalmere, NSW, Australia). Photosynthetically active radiation (PAR; μmol/m^2^/s) was recorded at the top of the chamber manually every 5 minutes using an Asensetek Lighting Passport (Asensetek, Taipei, Taiwan). VOCs were collected from the enclosures using a sorbent tube containing Tenax TA (Markes International Ltd, Llantrisant, U.K) connected to an air pump (AirChek 2000; SKC Inc., Eighty-Four, PA, USA) flowing air at 200mL/min for 30 minutes. Branches were allowed 30 minutes to acclimate to conditions within the enclosure before VOC sampling commenced. Background (control) enclosure samples were taken at the beginning and end of each day. Post-sampling, tubes were maintained at 4°C until analysis by GC-MS. Sampling occurred over a two-week period in January 2020 and again in March 2020. After VOC sampling, the branch was removed and subsequently dried in a fan-forced convection drying oven (Model TD-78T-2-D, Thermoline Scientific, Wetherill Park, NSW Australia) at 65 °C for 7 days before weighing. Sorbent tubes were analysed by thermal desorption GC-MS using the same equipment and protocols described in Lawson et al., (2020; doi:10.3389/fmars.2020.00106).